Legal Philosophy Perspective Toward Post-Divorce Child Custody in Indonesia - Damayanti, Sabrina; Betary, Sevia Ayu; Pitriani, Winda; Sihombing, Amanda Jessica (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This article discusses child custody after divorce of parents from the perspective of legal philosophy and the best interests of the child, legal philosophy, looking for the best application of child custody between the two and analyzing the factors that cause judges to decide on single and joint custody. The research method used is normative legal research using statutory and conceptual approaches. The results of the study state that joint child custody has more benefits in preventing children as objects of custody ownership in parental disputes and ensuring the psychological condition of children is maintained in the context of child development. In addition, in practice, judges still apply hadhanah singly as stipulated in the Compilation of Islamic Law, but there one PA Decision, PA Gedong Tataan Decision Number: 0334/Pdt.G/2019/PA Gdt which decides child hadhanah comprehensively and refers to the best interests of the child and sees more maslahah for the child, rather than the interests of the parents